PENGGUNAAN KARYA CIPTA FONT ‘OM TELOLET OM’ PADA PRODUK GREENFIELDS: The Use of Copyright Works in the the Form of Font ' Om Telolet Om' on Greenfields Product - Izabelle, Stella Monica; Nugrahani, Rr. Aline Gratika (AMICUS CURIAE, 2024)
As the owner of the ‘Om Telolet Om’ font, Arwan OD objected to using his font for the Greenfields brand. The font is used in writing attached to the Greenfields milk packaging. This study aims to find out how the Copyright Law protects fonts as copyrighted works and whether the use of the ‘Om Telolet Om’ font by Greenfields products is a copyright infringement. The research uses normative legal research methods, with secondary data supported by primary data. Based on the results of the research, it is known that based on Article 40 of the Copyright Law Number 28 of 2014, fonts are copyrighted works in the field of calligraphy art so the use of the font ‘Om Telolet Om’ without permission on greenfields milk packaging is a violation of the economic rights of the creator.